In Vitro Fertilization Versus Mild Stimulation Intrauterine Insemination in Women Aged 40 and Older. (April 2017) - Bou Nemer, Laurice; Weitzman, Vanessa N.; Arheart, Kristopher L.; Barrionuevo, Marcelo J.; Christie, Daniel R.; Mouhayar, Youssef; Hoffman, David I.; Maxson, Wayne S.; Ory, Steven J.
Introduction: The objective of this study was to compare clinical pregnancy rates (PRs) and pregnancy outcomes (POs) in patients undergoing in vitro fertilization (IVF) and a specific controlled ovarian hyperstimulation (mild-stimulation or mini-stim) and intrauterine insemination (IUI) protocol in women older than 40. Methods: It is a retrospective chart review of 770 cycles of all women aged 40 and older who underwent a first cycle of either IVF or mini-stim IUI between the years 2007 and 2012 at a single infertility center. Results: The PR in all women aged 40 and above was 12% (65/531) for IVF and 5% (13/239) for mini-stim IUI ( P = .004). When divided into age-groups, the PR of IVF at age 40 was superior to that at age 41 and above (15% vs 7%, P = .002), while the PR of mini-stim IUI remains similar (3% vs 7%, P = .307). When comparing the outcomes of the 2 treatments in the different age-groups, it showed that in women aged 40, IVF PR was superior to that of mini-stim IUI (15% vs 3%, P = .032); while in women aged 41 and above, IVF and mini-stim IUI have similar PR (7% vs 7%, P = .866). When POs were compared, the rate of live birth per cycle initiated was 9.2% for IVF versus 1.28% for mini-stim IUI ( P < .001). Conclusions: While IVF and mini-stim IUI were found to have similar PRs in women aged 41 and above, POs are significantly better in IVF. A larger study is required to clarify the above results.